Oxygen anomalous diffusion during photooxidation of polypropylene - José William de Lima Souza; Lucas Cordeiro de Oliveira; Taynah Pereira Galdino; Marcus Vinicius Lia Fook; Rômulo Feitosa Navarro (Polímeros, 2025)
Abstract This research paper is about the calculation of the diffusion coefficient and the oxygen concentration profile along polypropylene samples exposed to photooxidation in a dry environment. In this degradation process, oxygen diffusion is anomalous, as it is affected by structural modifications that occur over the exposure time. Thus, the diffusion coefficient starts to depend on time and the common solutions for Fick's 2nd Law for diffusion become inoperative for importante time intervals. In this work, a modification is proposed in the calculation of the diffusivity and, consequently, of the solution for the oxygen concentration profile in diffusion.